Pengembangan Bahan Ajar Sejarah Lokal Kalimantan Barat Berbasis E-Modul - Ika Rahmatika Chalimi (Universitas Majalengka, 2023)
Based on the results of the needs analysis, the learning conditions of local history are still not optimal. The teacher still focus on learning general history and has not been maximized in teaching local history material limited spesific learning resources. Problems of a local history learning can be solved through the development of e-module-based teaching materials designed to facilitate students to learn independently. This development research was created in an effort to assist teachers in teaching local history through e-module-based teaching materials with the application Adobe Flash CS version 6. The e-module-based teaching material design consists of a title page, table of contents, basic competency information, introduction to e-modules, scope, learning objectives, learning materials, evaluations and bibliography. The initial validation test of local history e-module products is carried out with media experts and local history material experts. After the expert validation test it was stated to be advanced, then a small-scale and large-scale feasibility test was carried out at the SMAN 6 Pontianak. The evaluation of local history teaching materials based on e-modules can be said to be feasible but there are a number of things that must be revised to be products that can be implemented in the classroom. Keywords: development, e-module-based teaching materials, local history. Berdasarkan hasil analisis kebutuhan, kondisi pembelajaran sejarah lokal masih belum optimal. Guru masih berfokus pada pembelajaran sejarah secara umum dan belum maksimal dalam mengajarkan materi sejarah lokal dengan keterbatasan sumber belajar yang spesifik. Permasalahan pembelajaran sejarah lokal tersebut dapat diatasi melalui pengembangan bahan ajar berbasis e-modul yang dirancang untuk memfasilitasi siswa belajar secara mandiri. Penelitian pengembangan ini dibuat sebagai upaya untuk membantu guru dalam mengajarkan sejarah lokal melalui bahan ajar berbasis e-modul dengan aplikasi Adobe Flash CS versi 6. Desain bahan ajar berbasis e-modul terdiri dari halaman judul, daftar isi, informasi kompetensi dasar, pengantar e-modul, ruang lingkup, tujuan pembelajaran, materi pembelajaran, evaluasi dan daftar pustaka. Uji validasi awal produk e-modul sejarah lokal dilakukan dengan ahli media dan ahli materi sejarah lokal. Setelah uji validasi ahli dinyatakan layak untuk dilanjutkan, kemudian dilakukan uji kelayakan skala kecil dan skala besar di SMAN 6 Pontianak. Hasil evaluasi bahan ajar sejarah lokal berbasis e-modul dapat dikatakan layak namun ada beberapa hal yang harus direvisi untuk menjadi produk yang dapat diimplementasikan di kelas. Kata kunci: pengembangan, bahan ajar berbasis e-modul, sejarah lokal.